Atypical cardioversion in unstable arrhythmia caused by clavicle surgery. (December 2017) - Bushuven, Stefan; Langenhan, Ronny
Abstract: We report on a 54-year old male with traumatic brain injury, flail chest and floating shoulder undergoing intramedullary stabilization of a midshaft clavicle fracture in beach chair position. Intraoperatively the patient developed instable atrial fibrillation triggered by implantation of intramedullary nail. Secondary this case shows feasibility of cardioversion in latero-lateral electrode-position due to inaccessible standard positions and patient fixation between the operation table and the X-ray apparatus.